2019
DOI: 10.26719/emhj.19.035
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean dietary patterns and risk of type 2 diabetes in the Islamic Republic of Iran

Abstract: Background: More than 1% of urban Iranians aged >20 years develop type 2 diabetes annually. A major contributing factor is overweight due to energy imbalance and poor quality diet. Even though there are reports on the beneficial effects of some isolated foods on glucose metabolism, researchers are increasingly focusing on dietary patterns versus single foods. Aims: The aim of this study was to evaluate the association between adherence to a Mediterranean diet and risk of type 2 diabetes. Methods: The current s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…However, frequent fish consumption (more than twice per week) was found to be a significant risk factor for hyperglycemia (OR = 1.496). Inconsistent with this observation, some studies have not reported a significant association between fish consumption and diabetes [ 27 ], and some studies have reported an inverse relationship between fish consumption and the risk of diabetes [ 28 ]. These inconsistencies can in part be explained by the differences in the quantity and type of fish consumed, and also the differences in cooking methods in different food cultures [ 27 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, frequent fish consumption (more than twice per week) was found to be a significant risk factor for hyperglycemia (OR = 1.496). Inconsistent with this observation, some studies have not reported a significant association between fish consumption and diabetes [ 27 ], and some studies have reported an inverse relationship between fish consumption and the risk of diabetes [ 28 ]. These inconsistencies can in part be explained by the differences in the quantity and type of fish consumed, and also the differences in cooking methods in different food cultures [ 27 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In impoverished nations, these parasites are mostly to blame for illness and mortality [1,2]. Due to poor environmental cleanliness, personal hygiene practices, and general health system weaknesses, intestinal contaminations are very common in underdeveloped nations [3][4][5]. About 3.5 billion people are afected globally, of which 450 million sufer from intestinal parasite diseases, which are thought to be the cause of 200,000 annual deaths [6].…”
Section: Introductionmentioning
confidence: 99%
“…Most local farmers in many countries that are developing use polluted or untreated water for irrigation and untreated or polluted human or animal dung as fertilizer, which contributes to increased transmission of intestinal parasitic (IP) contaminations and is to blame for the high rates of contamination with parasites [4]. Fruits and vegetables can be contaminated by protozoans (cysts and oocytes) and helminths (eggs and larvae), and humans get infected by consuming those contaminated fruits and vegetables without proper washing [5].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of diabetes in Iran was reported to be 8.94% in 2017, and it is projected to reach 13.64% by 2045 (Cho et al., 2018 ). In Iran, more than 1% of the urban inhabitants whose age is >20 years old are annually diagnosed with T2DM (Ramezan et al., 2019 ), and this is thought to be mostly associated with the unhealthy diet and sedentary lifestyle (Ketema et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%